Datawarehousing The Viable Solution To Modern Business Strategies (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Managing a business has never been easy. Trying  economic conditions make it even harder. The challenge is  to do more with less and to make better decisions for the  growth of the modern business. Having immediate access  to current, actionable information can make a huge  difference. “Business Intelligence therefore refers to a  set of tools and techniques that enable a company to  transform its business data into timely and accurate  information for the decisional process, to be made  available to the right persons in the most suitable  form.” Business Intelligence systems help the users make  the right decisions based on the available data. Over the last few years the pressure has been growing to  manage, integrate, analyse and act on increasing amounts  of information from all kinds of data sources. Business  Intelligence is not a new idea. The largest and best managed organizations in the world have been making  use of it for more than a decade. Along the way, the  giants that pioneered BI made an important discovery  –the path to true business intelligence passes through  a Data Warehouse. With these modern Data Warehouse  Architectures flexibility and responsiveness is greatly  improved while minimising the total cost of ownership.  “A data warehouse is a subject-oriented, integrated,  time variant and non-volatile collection of data in  support of management decision making process.” A data warehouse is a relational database that is designed  for query and analysis rather than for transaction  processing. Modern Businesses today are not only  demanding analysis of data from its own operational  systems but also the ability to consume, filter and analyse  data from a broad range of external data sources.  Business intelligence systems provide the ability to answer  these critical questions by turning the massive amount of  data from operational systems into a format that is current,  actionable, and easy to understand. THE DESIGN OF ADATAWAREHOUSE INVOLVES 1) Acquisition of data for the warehouse. 2) Ensuring that Data Storage meets the query requirements efficiently. 3) Giving full consideration to the environment in which  the data warehouse resides. Both quality and consistency of data are major  concerns. There are many different issues faced in the implementation of a Data Warehouse, its Architecture and  Design. So, this paper highlights the need of Data Warehousing in  the modern business strategies, features of data warehouse, the different issues faced in the implementation of the data warehouse and different  concerns of the data warehouse architecture and design. It  also discusses the solution to these issues along with the  research and case studies that are documented in this  field.
Keywords: Data Warehousing; Business Intelligence; Operational Databases; OLTP; OLAP